2021
DOI: 10.1007/s11467-020-1039-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between repeating bursts of FRB 121102 and giant pulses from Crab pulsar and its applications

Abstract: There are some similarities between bursts of repeating fast radio bursts (FRBs) and giant pulses (GPs) of pulsars. To explore possible relations between them, we study the cumulative energy distributions of these two phenomena using the observations of repeating FRB 121102 and the GPs of Crab pulsar. We find that the power-law slope of GPs (with fluence ≥130 Jy ms) is 2.85 ± 0.10. The energy distribution of FRB 121102 can be well fitted by a smooth broken power-law function. For the bursts of FRB 121102 above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Cordes & Wasserman 2016). The giant pulses of Crab pulsar also show a power-law distribution (Popov & Stappers 2007;Lyu et al 2021). A power-law distribution of energy is a natural predication of self-organized criticality theory (Bak et al 1987;Aschwanden 2011).…”
Section: Energy Distributionmentioning
confidence: 98%
“…Cordes & Wasserman 2016). The giant pulses of Crab pulsar also show a power-law distribution (Popov & Stappers 2007;Lyu et al 2021). A power-law distribution of energy is a natural predication of self-organized criticality theory (Bak et al 1987;Aschwanden 2011).…”
Section: Energy Distributionmentioning
confidence: 98%
“…It has also become simpler to define the FRB class by its luminosity as more FRBs are associated with host galaxies. Therefore, we propose an FRB radio spectral energy threshold of 10 29 erg Hz −1 , which includes all FRBs and excludes all other millisecond radio transients associated with well defined Galactic classes (e.g., Crab giant pulses; Cordes et al 2004;Lyu et al 2021). With this definition, a repeating FRB is defined as any source with multiple bursts with energy greater than 10 29 erg Hz −1 .…”
Section: Frb and Prs Populationsmentioning
confidence: 99%
“…Their origin from magnetars is preferred nowadays (Zhang 2020). FRBs take similarities to GPs (Lyu et al 2021) and can be viewed as super-GPs from young and rapidly spinning pulsars (Cordes & Wasserman 2016;Katz 2016;Lyutikov et al 2016). Previously, the authors Wang et al (2018) revealed evidence indicating that the repeating FRBs originate from starquake induced behaviour.…”
Section: Transient Phenomenamentioning
confidence: 99%